Peran Orang Tua dalam Meningkatkan Prestasi Belajar Siswa Kelas IV pada Mata Pelajaran Al-Qur’an Hadits di MIS Al Amanah Bedahan - Erna Wati; Eva Rahmawati; Khoirunisa Khoirunisa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The study aims to investigate the role of parents in improving students' academic achievement in Al-Qur'an Hadith subject and identify supporting and inhibiting factors. The research uses a qualitative approach with descriptive qualitative method. Data collection techniques include observation and interviews. (1) Parental Role: Parents play a significant role in improving their children's academic achievement by providing necessary facilities, such as: Stationery and learning materials, A dedicated study space, Supporting books, Acting as motivators to boost their children's confidence, Serving as educators, guides, motivators, and facilitators.(1) Supporting and Inhibiting Factors: Busy schedules and limited time for parents to guide their children, Children's lack of interest in learning and excessive gadget use or TV watching, Peer influence and environment can impact students' academic performance